THE URGENCY OF THE STUDY OF THE EDUCATIONAL DISCIPlINE COURSE «MANAGEMENT OF CULTURE AND ART» IN FACULTIES OF MUSIC OF UKRAINIAN HIGHER EDUCATIONAL ESTABLISHMENTS - Карась, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the urgency of the study of the student course «Management of culture and art» in Faculties of Music of Ukrainian higher educational establishments. The author analyses the experience of its status value in Ukraine and Russia and proposes her vision of the concept of the course. The table of contents of the educational discipline includes the following main components: theoretical background of the management and administrative process; management of particular events in the field of art; show business management; advertising and PR.